Cooling of alpaca spermatozoa using an extender with the addition of different percentages of seminal plasma - Bertuzzi, Mariana Lucía; Torres Mamani, Edita Yola; Pérez Durand, Manuel Guido; Huanca Mamani, Teodosio; Giuliano, Susana María; Carretero, María Ignacia (Elsevier, 2024)
The objective of this study was to evaluate the effect of the addition of different percentages of seminal plasma (SP) during the cooling at 5 °C of alpaca spermatozoa from vas deferens. Fifteen pools of sperm from vas deferens were evaluated and then divided into four aliquots that were diluted to a final concentration of 30 × 106 sperm/ml with either: (1) Tris with 20% egg yolk (T-EY) (control, 0% SP), (2) T-EY with 10% SP, (3) T-EY with 25% SP, and (4) T-EY with 50% SP. Samples were cooled at 5 °C and the following sperm parameters were evaluated after 24 and 48 h of storage: motility, viability, membrane function, acrosome integrity, morphology, and chromatin condensation. Motility was also evaluated after 72 h of storage. A significant decrease in progressive and total sperm motility was observed in samples cooled with 50% SP with respect to all diluted samples, while these parameters were preserved in samples cooled with 0%, 10%, and 25% SP. The percentages of sperm viability, normal morphology, and highly condensed chromatin did not change after the cooling process and were similar between cooled samples. Although a significant decrease was observed in the percentage of spermatozoa with functional membranes and with an intact acrosome in all refrigerated samples compared to raw sperm, the greatest decrease was observed in samples cooled with 50% SP. No advantage was observed from the addition of SP to alpaca spermatozoa obtained from vas deferens and being cooled. In addition, to preserve the sperm motility of cooled samples for up to 72 h, it should be recommended to include a 10% SP in the extender.